2022
DOI: 10.5812/jhealthscope-124245
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Hospital Admission for Epilepsy in Kerman, Iran

Abstract: Background: This study aimed to investigate the relation between air pollution and epilepsy admissions in Kerman, Iran. Methods: In this ecological study, the concentrations of ambient air pollutants and meteorological data were obtained from Kerman Environmental Protection Agency and Kerman Meteorology Organization, respectively. Additionally, epilepsy admission data were obtained from Kerman’s Shafa hospital epilepsy registry. Generalized additive models with lags up to 7 days were used to estimate rate rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…33 Therefore, eight studies were eligible for inclusion in the meta-analysis (Figure 1), and they all focused on the association between short-term exposure to air pollutants and seizures. 9,10,18,[34][35][36][37][38] The pollutants that were assessed in these eight studies are PM 10 (n = 7), SO 2 (n = 7), NO 2 (n = 6), O 3 (n = 6), CO (n = 5), PM 2.5 (n = 5), and PM 10-2.5 (n = 1). The distributions of the mean pollutant concentrations are available in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Therefore, eight studies were eligible for inclusion in the meta-analysis (Figure 1), and they all focused on the association between short-term exposure to air pollutants and seizures. 9,10,18,[34][35][36][37][38] The pollutants that were assessed in these eight studies are PM 10 (n = 7), SO 2 (n = 7), NO 2 (n = 6), O 3 (n = 6), CO (n = 5), PM 2.5 (n = 5), and PM 10-2.5 (n = 1). The distributions of the mean pollutant concentrations are available in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we searched the reference lists of all studies included in this review and used the “cited by” feature of SCOPUS to screen for eligibility articles that cited included studies. This process was completed using Web of Science for one study that was not indexed in Scopus 18 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that people poisoned with organophosphate compounds show cardiovascular symptoms such as hypotension and arrhythmia (5,6). Also, other studies have shown environmental and occupational exposure can harm health (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are a group of lipophilic organic compounds consisting of two or more fused aromatic rings, which enter the environment (13,14).…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%